2018
DOI: 10.3390/ijerph15050967
|View full text |Cite
|
Sign up to set email alerts
|

The Relative Contribution of Dietary Habits, Leisure-Time Exercise, Exercise Attitude, and Body Mass Index to Self-Rated Health among College Students in Taiwan

Abstract: Background: Self-rated health (SRH) is consistent with objective health status and can serve as a global measure of health status in the general population. The purpose of this study is to find the connections of dietary habits, leisure-time exercise, exercise attitude, and body mass index (BMI) to SRH among college students. Methods: The “dietary–exercise attitude and SRH” questionnaire was developed to investigate college students in Taiwan through the Internet. Partial least squares structural equation mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 21 publications
3
8
0
Order By: Relevance
“…Exercise, even for a short time every day, may effectively reduce mentally unhealthy days. The results of this study were similar to those of previous studies conducted on adults in various regions [20][21][22][23]. Another study has shown that moderate-to-vigorous physical activity of fewer than 30 minutes/day is associated with a reduced mortality rate [24], thereby implying that even short exercise sessions may contribute to better health and fewer mentally unhealthy days.…”
Section: Discussionsupporting
confidence: 89%
“…Exercise, even for a short time every day, may effectively reduce mentally unhealthy days. The results of this study were similar to those of previous studies conducted on adults in various regions [20][21][22][23]. Another study has shown that moderate-to-vigorous physical activity of fewer than 30 minutes/day is associated with a reduced mortality rate [24], thereby implying that even short exercise sessions may contribute to better health and fewer mentally unhealthy days.…”
Section: Discussionsupporting
confidence: 89%
“…Specifically, there are many studies that have shown a positive relationship between physical practice and mental health [35,36]. Among others, it has been observed that physical practice has a positive impact on mood [37,38], it decreases anxiety and depression symptoms [39,40] and it improves self-perceived health appraisal [41,42]. This phenomenon has been observed both after a single session of physical activity and after a physical exercise program [43], indicating the broad potential such behaviors have in order to improve people's health and well-being.…”
Section: Introductionmentioning
confidence: 99%
“…With a prevalence of sedentary lifestyles and poor dietary habits, many people suffer from obesity-induced diseases [1]. Participation in sports can promote health and help to avoid these diseases.…”
Section: Introductionmentioning
confidence: 99%